2018
DOI: 10.1242/dev.156869
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional quantitative analysis of mRNA expression within intact vertebrate embryos

Abstract: For decades, in situ hybridization methods have been essential tools for studies of vertebrate development and disease, as they enable qualitative analyses of mRNA expression in an anatomical context. Quantitative mRNA analyses typically sacrifice the anatomy, relying on embryo microdissection, dissociation, cell sorting and/or homogenization. Here, we eliminate the trade-off between quantitation and anatomical context, using quantitative in situ hybridization chain reaction (qHCR) to perform accurate and prec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(112 citation statements)
references
References 52 publications
7
105
0
Order By: Relevance
“…demonstrated that in situ HCR v2.0 overcomes the longstanding tradeoff between RNA quantitation and anatomical context, using optimized standard HCR probe sets to perform analog mRNA relative quantitation (qHCR imaging) with subcellular resolution within whole-mount vertebrate embryos (Trivedi et al, 2018). Precision increases with probe set size (Trivedi et al, 2018), so the prospect of using large unoptimized split-initiator probe sets is highly appealing. To test mRNA relative quantitation with automatic background suppression, we redundantly detected target mRNAs using two split-initiator probe sets each triggering a different spectrallydistinct HCR amplifier ( Figure 5AB).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…demonstrated that in situ HCR v2.0 overcomes the longstanding tradeoff between RNA quantitation and anatomical context, using optimized standard HCR probe sets to perform analog mRNA relative quantitation (qHCR imaging) with subcellular resolution within whole-mount vertebrate embryos (Trivedi et al, 2018). Precision increases with probe set size (Trivedi et al, 2018), so the prospect of using large unoptimized split-initiator probe sets is highly appealing. To test mRNA relative quantitation with automatic background suppression, we redundantly detected target mRNAs using two split-initiator probe sets each triggering a different spectrallydistinct HCR amplifier ( Figure 5AB).…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative properties of in situ HCR enable gene expression queries in two directions (Trivedi et al, 2018): read-out from anatomical space to expression space to discover co-expression relationships in selected regions of the specimen; conversely, read-in from multidimensional expression space to anatomical space to discover those anatomical locations in which selected gene co-expression relationships occur. Quantitative read-out and read-in analyses provide the strengths of flow cytometry expression analyses, but by preserving anatomical context, they enable bi-directional queries that open a new era for in situ hybridization (Trivedi et al, 2018). In situ HCR v3.0 using large split-initiator probe sets enhances accuracy and precision for read-out/read-in using either qHCR relative quantitation (Trivedi et al, 2018) or dHCR absolute quantitation (Shah et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations